MMP-2 and MMP-9 Activities and TIMP-1 and TIMP-2 Expression in the Prostatic Tissue of Two Ethanol-Preferring Rat Models - Beatriz Aparecida Fioruci-Fontanelli; Luiz Gustavo A. Chuffa; Leonardo O. Mendes; Patricia Fernanda F. Pinheiro; Flávia Karina Delella; Cilmery S. Kurokawa; Sérgio Luis Felisbino; Francisco Eduardo Martinez (Analytical Cellular Pathology)
We investigated whether chronic ethanol intake is capable of altering the MMP-2 and MMP-9 activities and TIMP-2 and TIMP-1 expression in the dorsal and lateral prostatic lobes of low (UChA) and high (UChB) ethanol-preferring rats. MMP-2 and MMP-9 activities and TIMP-1 and TIMP-2 expression were significantly reduced in the lateral prostatic lobe of the ethanol drinking animals. Dorsal prostatic lobe was less affected showing no significant alterations in these proteins, except for a reduction in the TIMP-1 expression in UChA rats. These important findings demonstrate that chronic ethanol intake impairs the physiological balance of the prostate extracellular matrix turnover, through downregulation of MMPs, which may contribute to the development of prostatic diseases. Furthermore, since these proteins are also components of prostate secretion, the negative impact of chronic ethanol intake on fertility may also involve reduction of MMPs and TIMPs in the seminal fluid.